POTENSI PENCAHAYAAN ALAMI PADA RUMAH SUSUN SARIJADI BANDUNG - Yasmin Suriansyah (Universitas Katolik Parahyangan, 2014)
Apartment Sarijadi Bandung (ASB) is a first-generation mass public housing (1975) in Bandung Indonesia is intended as mass public housing for the lower middle income, and until now still inhabited. ASB is the only apartment in the city designed as cluster typology with one staircase lined to four dwelling units, so that the wall has openings on outer façade and inner court facade. One of its design approaches is to optimize natural lighting with wall openings on those two-façade. This study aims to determine the extent of a natural lighting at ASB that is designed with optimization approach of the natural lighting. This study used quantitative methods. Field surveys conducted to obtain data of (1) physical spatial configurations of architectural elements, and (2) illuminant of the residential units, which will be used for analyzing how much the natural lighting potential in the residential units at ASB. The finding is the innovations of disclosure of influence factors of the architectural physic-spatial configuration to day lighting potential in vertical residential building typology as in the ASB. It is a useful new finding to be applied in supporting the development of science and technology and procurement related to vertical housing that provide opportunities for better life quality and energy efficiency in urban areas.Keywords: Daylight, physic-spatial configuration, apartment, Sarijadi Bandung Indonesia